An updated review on abnormal epigenetic modifications in the pathogenesis of systemic lupus erythematosus - Zhou, Xingyu; Zhou, Shengnan; Li, Yaping (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. The inconsistent prevalence of SLE between monozygotic twins suggests that environmental factors affect the occurrence of this disease. Abnormal epigenetic regulation is strongly associated with the pathogenesis of SLE. Epigenetic mechanisms may be involved in the development of lupus through DNA methylation, histone modification, noncoding RNAs, and other modifications. This review aims to show numerous studies as a treasure map to better understand the effects of aberrant epigenetic modification in the onset and development of SLE, which will benefit the current basic research and provide potential diagnostic biomarkers or therapeutic targets for SLE.